Active Compounds in Broadleaf Mahogany (Swietenia macrophylla) Seeds as Antiaging Agent Based on Molecular Docking Study - Batubara, Irmanida; Aulia Putri, Faradina; Tohir, Dudi; Fira Asoka, Shadila (Study Program of Chemistry - Alauddin State Islamic University of Makassar, 2023)
The appearance of brown spots and wrinkles can be a sign of aging which can increase the risk of cancer. Compounds in broadleaf mahogany seeds (Swietenia macrophylla) contains many compounds and is known to have anticancer activity. The purpose of this study was to determine the compounds in the seeds of these plants have the potential to antiaging by analyzing their molecular docking interaction on the MMP-1 enzyme (matrix metalloproteinase), NEP (neprilysin), PPO3 (polyphenol oxidase), and as a support for the search for anticancer compounds. Two compounds that have the potential as strong inhibitors towards MMP-1 and PPO3 enzymes, namely β-cytostenone and 3β-hydroxystigmast-5-en-7-on which is a steroid group, as well as germacrena A and germacrena D which are terpenoids. Only compound 3β-hydroxystigmast-5-en-7-on which has the potential as a strong inhibitor of the NEP enzyme. All compounds have the potential to be strong inhibitors according to the Lipinski rule. Only compounds which binds to the PPO3 enzyme which has better activity than natural ligand based on ΔG and Binding Site Similarity (BSS) values.